In Search Of Progressive Nationalism - A. I. Samorodov (Vestnik MGIMO-Universiteta, 2021)
Book review: Cörüt I., Jongerden J. (ed.). 2021. Beyond Nationalism and the Nation-State: Radical Approaches to Nation. Routledge. 226 p. ISBN 9780367684020